Investigation of Geometric Characteristics on the Lubricant Performance of Thrust Bearing with Cavitation - L. Kailei; C. Jiayuan; Z. Haoran; Z. Lin; W. Xuze; C. Yu (Journal of Applied Fluid Mechanics)
In this study, a mixed lubrication model that incorporates cavitation can be developed to examine the evolution of hydrodynamic lubrication in spiral grooved thrust bearing. The simulation model includes cavitation effects and utilizes hexahedron unit grid division technology to enhance the mesh quality of spiral grooved thrust bearing. The computational model would be crafted to provide an efficient solution while maintaining the ability to accurately represent the hydrodynamic behavior of spiral grooved thrust bearing. The simulation model considers the impact of geometric characteristics and operational conditions, including the viscoelastic effect, transformation feature, and flow state, to enhance calculation ability. The validity and practicality of the proposed approach are corroborated by experimental results. Additionally, an analysis of the hydrodynamic behavior of spiral grooved thrust bearing can be conducted, and the simulation results elucidate the relationship between key parameters and lubrication performance, offering valuable insights for the optimization of spiral grooved thrust bearing.